Electronic banking system in nigeria: possible clogs in the wheel (2009)
Banking system has gone beyond the traditional brick and mortal bank where every banking transaction has to be carried out with paper cash and where the presence of the parties to the transaction are always required. With the introduction of the electronic banking system most of the activities being carried out inter praesentes are now being done through electronic media. Some concepts of electronic banking system are discussed in this paper and some basic challenges which may constitute clogs to the wheel of progress of this system are revealed in general term with the purpose of suggesting the way forward.